Implementation of ESD in language education in Finland – Higher education language teachers’ views and experiences - Maijala, Minna; Saikkonen, Loretta; Malessa, Eva; Kuusalu, Salla-Riikka (Walter de Gruyter GmbH, 2026)
Language education offers tremendous potential for implementing Education for Sustainable Development (ESD) in higher education (HE), as the pedagogical processes of language teaching and ESD are complementary to each other. Researchers have recognised this potential, but it has yet to be fully utilised. The study analyses HE language teachers’ (n = 43) questionnaire data to determine how often they incorporate different sustainable development (SD) dimensions into their teaching, and which factors are associated with the frequency of teaching SD. The data was analyzed using percentage distributions and Spearman’s correlation, while open-ended responses were analyzed using thematic categorization. Cultural sustainability was the most frequently integrated dimension into language teaching. A majority of teachers were motivated to teach SD, but only a third reported high self-efficacy in doing so. Similarly, only a third reported sufficient institutional support. Self-efficacy correlated with SD teaching motivation, and both correlated with the SD teaching frequency. Institutional support correlated with motivation and the frequency of teaching ecological and social sustainability. The challenges of teaching SD were related to time constraints and availability of teaching materials. Teachers who had access to SD materials were less likely to perceive time constraints as a barrier.